TSLP: contrasting roles in cancer - Poto, Remo; Marone, Gianni; Ziegler, Steven F.; Varricchi, Gilda (Frontiers in Immunology, 2025)
Thymic stromal lymphopoietin (TSLP) is an alarmin cytokine possessing a plethora of pleiotropic properties. Human and mouse TSLP exerts their activity via a heterodimeric complex composed of TSLP receptor (TSLPR) chain and IL-7Rα. TSLP is predominantly expressed by epithelial cells and keratinocytes but can also be produced by several immune cells and some cancers. TSLP activates a plethora of immune cells implicated in inflammation, angiogenesis and tumorigenesis. In addition to its role in barrier immunity, recent studies have a role for TSLP in cancer development. This includes both human hematologic cancers and several solid tumors (largely carcinomas). The role of TSLP in human and experimental cancers has been the focus of several studies, with somewhat contradictory findings. In this Review, we will highlight recent advances in TSLP immunobiology in the context of human and experimental cancers. We will also discuss recent findings demonstrating that an anti-TSLP monoclonal antibody (mAb) can exert a protective effect in a mouse model of colorectal cancer. The recent approval of an anti-TSLP mAb for asthma treatment also emphasizes the urgent need for additional research on the role of TSLP, a Janus cytokine, in tumorigenesis.